Novas evidências empíricas sobre a dinâmica trimestral do consumo agregado das famílias brasileiras no período 1995-2009 - Bernardo Patta Schettini; Cláudio Hamilton Matos dos Santos; Cláudio Roberto Amitrano; Gabriel Coelho Squeff; Márcio Bruno Ribeiro; Raphael Rocha Gouvêa; Rodrigo Octávio Orair; Thiago Sevilhano Martinez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper presents new econometric specifications for the quarterly behavior of the aggregate consumption of Brazilian households in the 1995-2009 period. It is argued, in particular, that the use of quarterly measures of both private disposable income (in chained 1995 prices) and the credit extended to households (as a % of GDP) as explanatory variables leads to well adjusted models within the sample with good out of sample performance - for the level of precision of our quarterly estimates four quarters out of sample is close to 99%. Moreover, the models presented in this paper point to values of the (approximated) private income elasticity close to 0.4 and credit and interest (semi) elasticities of household consumption close to 2% and -2%, respectively.
Keywords: E21; E27; C22; C52; C82; 330; Verfügbares Einkommen; Konsum; Brasilien